2003
DOI: 10.1021/jm030131l
|View full text |Cite
|
Sign up to set email alerts
|

Design, Parallel Synthesis, and Crystal Structures of Pyrazinone Antithrombotics as Selective Inhibitors of the Tissue Factor VIIa Complex

Abstract: Structure-based drug design (SBDD) and polymer-assisted solution-phase (PASP) library synthesis were used to develop a series of pyrazinone inhibitors of the Tissue Factor/Factor VIIa (TF/VIIa) complex. The crystal structure of a tripeptide-alpha-ketothiazole complexed with TF/VIIa was utilized in a docking experiment to identify the pyrazinone core as a starting scaffold. The pyrazinone core could orient the substituents in the correct spatial arrangement to probe the S1, S2, and S3 pockets of the enzyme. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…The coumarin skeleton was chosen as a fluorescent chromophore, and an azidophenyl moiety was introduced as the photoreactive part. [16][17][18] The probe CAFSA (6) was synthesized as shown in Fig. 9.…”
Section: Resultsmentioning
confidence: 99%
“…The coumarin skeleton was chosen as a fluorescent chromophore, and an azidophenyl moiety was introduced as the photoreactive part. [16][17][18] The probe CAFSA (6) was synthesized as shown in Fig. 9.…”
Section: Resultsmentioning
confidence: 99%
“…Kinetics of rTF⅐FVIIa Inhibition by G17905-Enzyme kinetic studies with a substituted benzamidine indicated that FVIIa active site inhibitors are competitive with respect to small peptidyl substrates and noncompetitive with respect to macromolecular substrate activation (70). So far, all published substituted benzamidine inhibitors of FVIIa bind to the standard active site conformation (71)(72)(73)(74)(75)(76). However, G17905 binds to the nonstandard active site conformation, raising the possibility that G17905 could follow different inhibition kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…Using the crystal structure of TF/VIIa bound to a tripeptide-␣-ketothiazole, hundreds of pyrazinone TF/VIIa inhibitors were prepared and tested in several serine protease enzyme assays (Parlow et al, 2003;South et al, 2003). The structure activity relationship of the pyrazinone inhibitors was used to develop PHA-927F, a potent, selective, nonpeptide inhibitor of TF/ VIIa.…”
mentioning
confidence: 99%